PENGARUH CARA PENGOLAHAN PANGAN TERHADAP KANDUNGAN IODINE PADA PANGAN YANG DIKONSUMSI BALITA DI WILAYAH ENDEMIK GAKI KECAMATAN MIOMAFFO BARAT KABUPATEN TTU TAHUN 2010 - Latunussa, Nindya M; Picauly, Intje; Aspatria, Utma (Pergizi Pangan DPD NTT, 2011)
Iodine is a type of mineral element of the second micro after iron substance which very important to human body. Iodine can be obtained by consuming daily food containing vegetables and meat essences. The research is aimed to discover the the influence of food processing manner towards the contents of iodine in food consumed by babies in the endemic area of gaki in the sub-district of miomaffo barat of ttu regency. A type of descriptive research is used with the method of cross sectional study. The amount of sample is 34 people gathered by means of purposive sampling method. The result of the research shows that (1); Food consumption pattern pervades the type, amount and food distribution frequency of baby which is in good category whereas, 61,76% of respondents possess a variety of sufficient food, the amount of food distributed is in the rate of 0,73-280,58 gr/capita/day and the common frequency of food is 3 times/day (100%), (2); Methods of food processing are; poaching and sauteing 31,83%, frying 26,32%, and dining a dish of raw vegetables and spicy sauce 10,52%, (3).